The retirement gamble [videorecording (DVD)] - Smith, Martin (Martin E.) (PBS Distribution, 2013)
The Retirement Gamble reveals how fees, self-dealing, and kickbacks bring great profits to Wall Street while imperiling the prospects of a secure future for individuals. The film questions who has the consumer's best interests in mind, and whether there is a better way to manage our retirements.